Insights into regulatory T-cell and type-I interferon roles in determining abacavir-induced hypersensitivity or immune tolerance - Cardone, Marco; Baghdassarian, Hratch M.; Khalaj, Maryam; Sivakumar, Kirthiram Krishnaveni; Hwang, SuJin; Gebreyohannes, Sintayehu; Takeda, Kazuyo; Jang, Yura; Lewis, Nathan E.; Norcross, Michael A.; Puig, Montserrat (Frontiers in Immunology, 2025)
IntroductionClinical use of several small molecule drugs may lead to severe T-cell-mediated idiosyncratic drug hypersensitivity reactions (iDHR) linked to HLA alleles, including abacavir (ABC) with HLA-B*57:01. Due to study limitations in humans, pathogenic networks in iDHR remain elusive. HLA transgenic murine models have been proposed to bridge knowledge gaps in tolerance and susceptibility to drugs.MethodsMice expressing HLA-B*57:01 and Foxp3-DTR/EGFP were generated to selectively deplete regulatory T-cells (Treg) with diphtheria toxin. ABC was administered for 8 days alone or together with cell- and cytokine-depleting antibodies. Cellular and transcriptomic responses were analyzed by RNA, flow cytometry and fluorescence methods.ResultsWhile CD8+ T-cell responses to ABC require HLA presentation, ABC also triggered mitochondrial stress in macrophages in vitro, independently of HLA. In vivo, Treg were the primary mechanism of drug tolerance controlling HLA presentation and costimulation by antigen presenting cells. Treg ablation uncovered immune adverse events linked to activation and proliferation of both drug-specific and bystander CD8+ T-cells through CD28-mediated pathways with support from CD4+ non-Treg. Type-I interferon (IFN-I) and cellular-stress pathways influenced the fate of lymph node cells responding to ABC, implicating innate immune cells such as macrophages and plasmacytoid dendritic cells in the development of T-cell responses against the drug. IFN-I and IL-2 were necessary for CD8+ T-cell differentiation and ABC-induced adverse reactions.ConclusionsThis study unveils novel immune mechanisms driven by drug and host-related factors required for in vivo reactions and sheds light on potential biomarker and therapeutic targets for managing and preventing severe and life-threatening iDHR.